2016
DOI: 10.1016/j.gaitpost.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Active vision task and postural control in healthy, young adults: Synergy and probably not duality

Abstract: In upright stance, individuals sway continuously and the sway pattern in dual tasks (e.g., a cognitive task performed in upright stance) differs significantly from that observed during the control quiet stance task. The cognitive approach has generated models (limited attentional resources, U-shaped nonlinear interaction) to explain such patterns based on competitive sharing of attentional resources. The objective of the current manuscript was to review these cognitive models in the specific context of visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 27 publications
3
46
2
Order By: Relevance
“…These reports are important because they contrast with the literature, showing that young participants sway significantly less in precise search tasks than in gaze-fixation tasks when these tasks are performed on a small visual display (e.g., Stoffregen et al, 2006Stoffregen et al, , 2007Rougier and Garin, 2007 ;Giveans et al, 2011 ;Rodrigues et al, 2013). In fact, when the participants did not, or were not allowed to, rotate their body parts (Stoffregen et al, 2006(Stoffregen et al, , 2007Rougier and Garin, 2007;Giveans et al, 2011;Rodrigues et al, 2013), the CNS could reduce COP and/or postural sway to perform the precise visual task (Bonnet and Baudry, 2016a). In our study, the participants were allowed to and needed to rotate their body parts.…”
Section: Secondary Results: Isolated Behaviors (Posture and Vision Alcontrasting
confidence: 58%
See 1 more Smart Citation
“…These reports are important because they contrast with the literature, showing that young participants sway significantly less in precise search tasks than in gaze-fixation tasks when these tasks are performed on a small visual display (e.g., Stoffregen et al, 2006Stoffregen et al, , 2007Rougier and Garin, 2007 ;Giveans et al, 2011 ;Rodrigues et al, 2013). In fact, when the participants did not, or were not allowed to, rotate their body parts (Stoffregen et al, 2006(Stoffregen et al, , 2007Rougier and Garin, 2007;Giveans et al, 2011;Rodrigues et al, 2013), the CNS could reduce COP and/or postural sway to perform the precise visual task (Bonnet and Baudry, 2016a). In our study, the participants were allowed to and needed to rotate their body parts.…”
Section: Secondary Results: Isolated Behaviors (Posture and Vision Alcontrasting
confidence: 58%
“…Secondly, if the participants were free to rotate their body as they pleased in various tasks, the interindividual variability of behaviors would be very high, with some participants rotating parts of their body (head and/or shoulder and/or lower back rotations) a great deal and rapidly, while other participants would move just a little and/or slowly. In such circumstances, comparing the amount of body movement in various conditions -as is typical in the literature on postural control (see Bonnet and Baudry, 2016a for a review and further details about existing models) -may be irrelevant. To reduce the disparities in this field of research, we performed a study in which the participants performed unrestricted eye and body movements by looking at complex large ecological images.…”
Section: Introductionmentioning
confidence: 99%
“…If we focus our attention on a specific type of dual-task paradigms involving posture, models of dualtask performance will include the main DT theories described above in addition to other particular models. Again, there is no consensus on a suitable cognitive model that explains postural control in dual-task situations (for a review, see [15]). Almost all of the proposed models (other than the synergistic model [16]) suggest that above a certain level of complexity, the two tasks being carried out compete for attentional resources.…”
Section: Posturementioning
confidence: 99%
“…In previous studies, the postural stability was measured while simply requiring the subjects to stand as stably as possible, without the need to pay attention to any concurrent visual task, whereas in our study, the standing stability was measured during concurrent active visual tasks (the SVV task). In a more recently published review article, significantly lower amplitude of the body displacement was reported under active visual tasks than under the control quiet stance task (Bonnet and Baudry, 2016). Although speculative, we wonder whether this may be the helping effect of the concurrent visual vertical perception processing that contributes to the comparable postural stability between AIS subjects and controls.…”
Section: Discussionmentioning
confidence: 99%